Reducing operational costs in a manufacturing system that incorporates quality assurances, probabilistic failures, overtime and outsourcing - Novarika, Wirda; Sinaga, Sony Bahagia; Prayogi, Satria Yudha (Eastern-European Journal of Enterprise Technologies, 2024)
This research focuses on the dynamic landscape of today’s competitive market, where production management must meet clients’ expectations for high-quality products and shorter lead times while managing internal disruptions due to inevitable defects and unpredictable equipment failures. Achieving these operational goals without compromising product quality, missing deadlines, or experiencing production disruptions is essential for minimizing operational expenses. The study examines the dynamics of the system’s operating costs through the development of models, mathematical formulations, optimization techniques, and algorithm proposals. It demonstrates the system’s convexity and establishes the optimal batch time for implementing the proposed methodologies. The research results show relevant failure costs of 3.51 %, overtime added costs of 4.57 %, outsourcing setup costs of 0.73 %, outsourcing variable costs of 41.82 %, quality-related costs of 2.98 %, in-house variable costs of 40.42 %, and in-house holding costs of 3.55 %. The study develops strategies for optimal overtime use to meet production targets without excessive labor costs and provides a structured framework for making informed outsourcing decisions that balance cost savings with quality and reliability considerations. Overall, the research provides a robust framework for reducing operational costs while maintaining or improving the quality and reliability of manufacturing processes